FORMATION OF DEONTOLOGICAL TRAINING OF FUTURE TEACHERS – THE FOUNDATION OF EDUCATION DEVELOPMENT - Tursunova Nilufar Samievna (Galaxy International Interdisciplinary Research Journal, 2021)
The article examines the professional behavior of future teachers, the importance of pedagogical etiquette and deontological training, the goals and objectives of pedagogical deontology.